4 - Challenges of Regulating Financial Service Provision in Cameroon in the Digital Age and a Globalised World - Cheka, Cosmas (Africa Development, 2018)
This article identifies some of the challenges of the digital revolution and globalisation to the regulation of financial services in Cameroon. It provides a reading of records from data collected from documentary and online sources. The results show that to be relevant, the regulation of especially the provision of financial services must take into account evolving concepts about the basis of the operation of the economy and business models. The concepts of ‘time’, ‘space’ and ‘being’, which are central to the ascription of legal responsibility, are also undergoing a re-definition as well as diverse challenges couched inter alia as state politics, globalisation and trade, money laundering and the financing of terrorism. The results are significant in alerting to the dire need for reform of the rules governing the provision of financial services. The pre-digital age rules on the ascription of legal responsibility as well as the basis on which the regulation of such services was founded have been profoundly redefined by the information, communication and technology (ICT) revolution and globalisation.